TESTING CAPM MODEL ON THE EMERGING MARKETS OF THE EUROPE - Kgudoykulov, DSc, professor Khurshid (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The paper examines if the Capital Asset Pricing Model (CAPM) is sufficient for capital asset valuation on the European emerging markets using monthly stock returns for five countries for the period of January 2008 to December 2013. To be more exact, it is tested if beta, as the systematic risk measure, is valid on observed markets by analyzing are high expected returns associated with high levels of risk, i.e. beta. My intention is to find if the relationship between expected return and risk is linear, if beta is a complete measure of the risk and if a higher risk is compensated by a higher expected return